Peran Corporate Social Responsibility dalam Memediasi Pengaruh Konsentrasi Kepemilikan dan Media Exposure terhadap Nilai Perusahaan Sektor Perkebunan di Indonesia (Jurnal Kendali Akuntansi, 2025)
This study aims to evaluate the influence of Ownership Concentration and Media Exposure on Firm Value, with Corporate Social Responsibility (CSR) acting as a mediating variable. The research focuses on plantation sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A purposive sampling technique was applied to select 12 companies, resulting in 48 observational data points. Data were analyzed using panel data regression with the assistance of EViews 12 software. The findings reveal that Ownership Concentration and Media Exposure significantly affect CSR. Furthermore, CSR has a positive influence on Firm Value. However, Ownership Concentration does not have a direct or indirect effect on Firm Value. Meanwhile, Media Exposure does not directly affect Firm Value, but it indirectly contributes through the mediation of CSR. These findings reinforce the role of CSR as a strategic signal in shaping market perceptions of corporate sustainability and reputation.